2014
DOI: 10.1002/wcs.1294
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processing, language typology, and variation

Abstract: The author has declared no conflicts of interest for this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…A bias for aligned structures is also found in phylogenetic models of linguistic evolution [3]: After controlling for contingencies of history (such as language contact and language shifts), languages are universally more likely to develop and maintain aligned expressions than the opposite. Such a correlation of neural processing and evolutionary developments might stem from a tight interlacing of comprehension and production processes [17] or from shared neural underpinnings [18,19], and would be consistent with other findings on how the brain's processing constraints shape the form of languages [20][21][22][23][24].…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…A bias for aligned structures is also found in phylogenetic models of linguistic evolution [3]: After controlling for contingencies of history (such as language contact and language shifts), languages are universally more likely to develop and maintain aligned expressions than the opposite. Such a correlation of neural processing and evolutionary developments might stem from a tight interlacing of comprehension and production processes [17] or from shared neural underpinnings [18,19], and would be consistent with other findings on how the brain's processing constraints shape the form of languages [20][21][22][23][24].…”
Section: Introductionsupporting
confidence: 85%
“…Our results demonstrate how new insights on the relationship between language production and the simplicity and prevalence of specific language structures critically rely on evidence from neural processes that underlie different syntactic variants in the earliest stages of sentence planning. This opens new avenues for research on the neural processes in language planning and speech production that go beyond the level of individual words [62,99,100] and beyond the small set of languages that have dominated the field so far [22,71,74,[101][102][103].…”
Section: Plos Biologymentioning
confidence: 99%
“…from functional typologists, e.g. Haspelmath, 2006Haspelmath, , 2009Hawkins, 1994Hawkins, , 2004Hawkins, , 2007Hawkins, , 2014Sinnemäki, 2014, as well, more recently, from psycholinguistics and the cognitive sciences, e.g. Bornkessel-Schlesewsky, Choudhary, Witzlack-Makarevich, & Bickel, 2008;Christiansen & Chater, 2008;Jaeger & Tily, 2011;MacDonald, 2013;McDaniel, McKee, Cowart, & Garrett, 2015; see also Bever, 1970).…”
Section: Conclusion and Looking Forwardmentioning
confidence: 99%
“…Recent research suggests that linguistic structures adapt to the sociocultural environment in which languages are spoken (Ladd et al, 2015 ). Since languages are acquired and used in different social contexts, those contexts may bias acquisition and usage: linguistic structures become adapted to these social niches and this, over time, may be reflected in typological distributions (Lupyan and Dale, 2010 ; Sinnemäki, 2014 ). Central ideas in this approach have been: Small communities with dense social networks, few adult learners, and a great deal of shared knowledge favor linguistic structures that are difficult for adults (e.g., irregularity in inflectional paradigms); Large communities with loose social networks, more adult learners, and less shared knowledge favor more regular and easier to learn linguistic structures (e.g., regularity in inflectional paradigms, transparency; Trudgill, 2011b ).…”
Section: Introductionmentioning
confidence: 99%
“…Processing difficulties that language users face are one of the driving factors behind language change if, following a usage-based approach to language, we assume that preferences in language use become conventionalized over time (e.g., Sinnemäki, 2014 ). It has been recently suggested that the processing difficulties that adults face in learning and using an L2 may end up having an effect on the (evolution of the) grammar of the native speakers as well (see e.g., Lupyan and Dale 2010 ; Bentz and Winter 2013 ; and references there).…”
Section: Introductionmentioning
confidence: 99%